Sustainable Production of Pulque and Maguey in Mexico: Current Situation and Perspectives - Valdivieso Solís, Dulce Gabriela; Vargas Escamilla, Carlota Amadea; Mondragón Contreras, Nayeli; Galván Valle, Gustavo Adolfo; Gilés-Gómez, Martha; Bolívar, Francisco; Escalante, Adelfo (Frontiers in Sustainable Food Systems, 2021)
Pulque is a traditional Mexican fermented, non-distilled alcoholic beverage produced by fermenting the fresh sap (aguamiel) collected from diverse Agave species. This beverage was produced and consumed since Pre-Hispanic times by Mesoamerican civilizations, mainly in the Mexican Central Plateau, and is one of the essential alcoholic beverages produced and consumed during several centuries in Mexico. By 1900, annual pulque production was 485.56 billion liters and was a consolidated economic activity. The production and consumption of pulque decreased significantly at the beginning of the 20th century for various socio-political reasons and increased beer consumption in Mexico. By 2019, annual pulque production was reported in 171,482 billion liters, representing 0.13% of Mexico's total beer production in 2020. Traditional pulque production still faces several significant limitations, including the disappearance of large agave plantations; the extent of time required (at least five years) to complete the plant maturation for aguamiel extraction; traditional production practices; and the lack of an efficient stabilization process of the fermented product resulting in low shelf life. In opposition, successful examples of the fermentation process's industrialization resulted in high-quality pulque production, with international exportation certification. In this contribution, we present a review of the most relevant aspects of the history and commercial relevance of pulque, the causes that resulted in its production debacle during the first half of the 20th century, the current situation of its traditional production, and the successful efforts of industrial production of the beverage. We describe recent results on the analysis of the physicochemical characteristics of aguamiel and on the microbiology of the beverage explored by metagenomic techniques that can be proposed as a baseline to redefine the quality criteria of the beverage and to define for the first time a microbiological core to optimize its production. We also describe the relevance of maguey cultivation species for aguamiel production as a fundamental element of agroforestry and the relevance of its sustainable production. Finally, we describe some successful examples of beverage industrialization and potential applications of several microorganisms isolated from aguamiel, pulque, aguamiel concentrates, and the maguey to produce bioactive compounds high-value products.